Further Investigations on Unconventional Slot Numbers in Concentrated Winding Electric Motors: Rotor Eccentricity and Conventional Methods for Torque Ripple Reduction - Königs Mike; Harmel Michael; Loehlein Bernd (Power Electronics and Drives, 2025)
Electric motors with unconventional slot numbers, especially prime numbers, have been shown to reduce cogging torque and torque ripple. Our previous study investigated an 8p12s servo motor topology known to be prone to cogging torque and torque ripple; in this publication, the research is expanded to a more robust 10p12s servomotor, including a comparison of the novel unconventional winding with a conventional topology with breadloaf magnets. Furthermore, Finite element method (FEM) simulations with rotor eccentricities are conducted to evaluate the impact of the novel topology on forces and torques under imperfect manufacturing. It is shown that the novel quadruple-layer topology with prime number of slots can effectively reduce cogging torque and torque ripple. Furthermore, the commonly used 10p12s servomotor topology can achieve similar performance using skewing and breadloaf permanent magnets. The novel topology is shown to be prone to torque ripple due to rotor eccentricity. Similar results to conventional concentrated windings can be achieved under imperfect manufacturing conditions.